Enhancing Employee Performance Through Job Satisfaction: The Impact of Environment, Rewards, and Support - Nuswantoro, Alvin Anggoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of work environment, rewards, and organizational support on employee performance, with job satisfaction as an intervening variable among permanent employees of the Bank Rakyat Indonesia (BRI) Branch Office in Purbalingga. Design/Methodology/Approach – This study employs a quantitative research design with descriptive and causal approaches. The research was conducted among permanent employees of the BRI Purbalingga Branch Office, with 105 respondents selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among work environment, rewards, organizational support, job satisfaction, and employee performance. Findings – The results indicate that work environment, rewards, and organizational support have positive and significant effects on employee job satisfaction and performance. Furthermore, job satisfaction significantly mediates the relationships between work environment, rewards, organizational support, and employee performance. These findings demonstrate that improving workplace conditions, providing appropriate rewards, and strengthening organizational support can enhance employee satisfaction and performance. Originality/Value This research is original in examining the combined effects of work environment, rewards, and organizational support on employee performance with job satisfaction as a mediating variable. The findings provide practical value by guiding managers to enhance employee satisfaction and performance through targeted organizational interventions.